Nitroglycerine Induced Acute Myocardial Infarction in a Patient with Myocardial Bridging. (4th March 2014) - Rujic, Dragana; Nielsen, Mette Lundgren; Veien, Karsten Tange; Pareek, Manan
Abstract : Muscle overlying an intramyocardial segment of a coronary artery is termed a myocardial bridge. The intramyocardial segment, the tunneled artery, is compressed during systole. The condition is generally benign but may occasionally cause myocardial ischemia, infarction, arrhythmia, or sudden cardiac death. We present a case regarding a 52-year-old man with exercise-induced angina who was diagnosed with a myocardial bridge overlying the left anterior descending artery. He was initially treated with beta-blockers and later received coronary bypass graft surgery.